Using rapid city surveys to inform municipal social policy an application in Cali, Colombia - Hentschel, Jesko 1962- (Policy research working paper, 2004)
"Many developing countries assign local governments increasing responsibilities in fighting poverty. This requires local social policy to go beyond the execution of centrally designed and funded education and health programs. Hence, local governments and their partners have both an opportunity and a need to analyze key local bottlenecks for poverty reduction and social development. Drawing on an example from Cali, Colombia, Hentschel describes a tool for such policy formulation at the local level a rapid city household survey. Although the survey uses pre-coded and closed- ended questions, it is contextual in the sense that it is tailor-made to social and economic conditions in Cali. The survey places particular emphasis on collecting key quantitative information, such as household welfare and service access, as well as qualitative information, such as service evaluations and population priorities. Combining the quantitative and qualitative data allows, for example, the mapping of population budget priorities or service satisfaction levels by welfare group. Rapid city household surveys could provide an important tool for the development of local social policies. This paper "a joint product of the Human Development Sector Unit, and the Finance, Private Sector, and Infrastructure Unit, Latin America and the Caribbean Region" is part of a larger effort in the region to support local and municipal governments in the formulation of social policies"--World Bank web site